UEFA against the champions? An evaluation of the recent rof the Champions League qualification - Csató, L. (Journal of Sports Economics, 2022)
The paper evaluates the impact of the only reform in the Champions Path of UEFA Champions League qualifying system, effective from the 2018/19 season. In contrast to previous studies, our methodology considers five seasons instead of only one to filter out any possible season-specific attributes. The chances of some national champions decrease much stronger than suggested by the reduction in the number of available slots. Since the negative effects depend to a large extent on the arbitrary cutoffs in the access list, we propose to introduce some randomness into the determination of entry stages.